Justice system's responses to the May 2008 xenophobic violence in South Africa and its impact on access to justice for migrants: a case study of greater Johannesburg - Nkea, Aleambong Emmanuel (My University, 2010)
ABSTRACT Xenophobia and its related violence have informed South African society since the fall of apartheid. Xenophobic beliefs find expression in public discourses and have shaped both state and society in South Africa. A research (Misago et al.: 2009: 2) on the May 2008 xenophobic violence in South Africa confirmed that: “62 people, including 21 South Africans, were dead; at least 670 wounded; dozens of women raped; and at least 100 000 persons displaced and property worth of millions of Rand looted, destroyed or seized by local residents and leaders”. The post-1994 constitutional state that South Africa has become is based on the values of „human dignity‟ and „equality‟ among others. While law formed the basis of a divided and racist state prior to 1994, law has also taken a fundamental role in recognizing the universality of the human rights for all who live in South Africa today. Creating a strong visibility of human rights within the law, however, is only one step in the process. How the law is implemented determines its real worth and effectiveness. While these progressive laws further distinguish South Africa as a state with outstanding legal commitments towards the universality of human rights, they have failed to find expression in the implementation process. This study examines how the criminal justice system responded to the May 2008 xenophobic violence in South Africa from the dimensions of legal and policy frameworks; legal processes; legal innovations; institutional issues; and context factors such as non-state policing and justice structures. It focuses on three key actors; the courts, the National Prosecuting Authority (NPA), and the South African Police Services (SAPS). To properly demonstrate the peculiar challenges faced by the SAPS and the NPA in responding to the May 2008 violence, the study draws on the challenges faced by the SAPS and the NPA in investigating and prosecuting other violent crimes in South Africa.